PERBANDINGAN PEMBACAAN QR CODE MENGGUNAKAN METODE STANDAR DAN METODE EUCLIDEAN DISTANCE - A.Y. Erwin Dodu; Deny Wiria Nugraha; Thia Wydia Astuti (Informatics Engineering Department of Halu Oleo University, 2018)
The Quick Response Code technology (QR Code) is a type of matrix Code developed by Denso Corporation, with the aim of being a Code of translators at high speed. In its application QR Code can use the standard method and Euclidean Distance method on the process of reading. The benchmark in this discussion is whether there is a difference between Standard method and Euclidean Distance method on QR Code technology by looking at estimated time and accuracy after decoding data and information.The method used is qualitative research method with the type of comparative research. Based on the results of the study, it can be seen the comparison of time estimation, the Standard method has a shorter process time than Euclidean Distance, because of the Standard method using Library Zxing. Library Zxing is an open source library that works for processing various types of 1 dimensional and 2-dimensional barcodes that can shorten the QR Code reading compared to Euclidean Distance. From the level of accuracy, both Standard methods and Euclidean Distance methods have almost the same accuracy level that is at the time of reading QR Code the result is the same with plaintext.Keywords—Comparison, Euclidean Distance, QR Code DOI: 10.5281/zenodo.1610994